THE DEVELOPMENT OF HADITH STUDIES IN EGYPT AFTER THE FALL OF BAGDÄ€D: The Study of the Contributions of Hadith Scholars in Egypt in the 8th-9th Hijri Century - Rizkiy, M. Inul (Nabawi: Journal of Hadith Studies, 2024)
This article explores the contributions of 8th-9th century Egyptian scholars and their influence on contemporary hadith studies. While the fall of BagdÄd is often seen as a period of decline for the Muslim world, this study argues that Islamic regions, including Egypt, remained intellectually active. This article aims to examine the development of Hadith in Egypt as one of the regions that developed after the fall of BagdÄd. The datas of this qualitative historical research were collected through documentation, with primary sources including historical texts of ulamÄ in 8th-9th century and hadÄ«th works by Egyptian scholars. The analysis was conducted using content analysis and presented narratively and descriptively. The study employs synchronic and diachronic approaches to analyze Egyptâ€™s social, political, and ideological dynamics while exploring the evolution of hadith studies. The findings reveal that Egyptian 8th-9th century scholars significantly advanced various genres, including commentaries on primary hadith texts, poetic works on hadith sciences, biographical texts, commentaries on â€˜ulÅ«m al-hadÄ«th, and takhrÄ«j. They influence contemporary hadÄ«th studies through the canonization of works and their impact on modern scholars.[Artikel ini membahas kontribusi ulama hadis di Mesir abad VIII-IX dan pengaruhnya terhadap kajian hadis kontemporer. Keruntuhan BagdÄd sering dianggap masa kemunduran dunia Islam, tetapi artikel ini berpendapat bahwa wilayah-wilayah Islam, termasuk Mesir, tetap aktif dalam mengembangkan keilmuan. Artikel ini ingin melihat perkembangan hadis di Mesir sebagai salah satu daerah yang berkembang pasca-BagdÄd runtuh. Data dalam penelitian historis-kualitaatif ini dikumpulkan dengan teknik dokumentasi. Data primer ialah kitab sejarah ulama abad VIII-IX dan kitab hadis ulama Mesir. Data dianalisis dengan analisis konten. Hasil analisisnya disajikan secara naratif-deskriptif. Penelitian ini juga menggunakan model sinkronis dan diakronis dalam ilmu sejarah untuk melihat dinamika sosial, politik, dan ideologi di Mesir serta mengeksplorasi perkembangan studi hadis di Mesir. Hasil dari penelitian ini menunjukkan bahwa ulama Mesir abad VIII-IX berhasil mengembangkan berbagai genre kajian ilmu hadis, meliputi syarah kitab hadis primer, nazam ilmu hadis, kitab biografi, syarah kitab â€˜ulÅ«m al-á¸¥adÄ«á¹¡, dan takhrÄ«j kitab. Pengaruh ulama Mesir bagi kajian hadis kontemporer meliputi kanonisasi karya dan pengaruh pada tokoh kontemporer.]